Test Anxiety: The Problem and Possible Responses - Deffenbacher, Jerry L. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper describes test anxiety as a significant psychological problem and outlines five possible responses that counselling can make to this problem. These options were evaluated against standards of professionalism, feasibility and empirical support. It was concluded that programs to develop self-control anxiety-management skills in the highly anxious had a great deal to offer in approaching this problem.